Gendered perceptions and socio-economic and spatial determinants of fear of crime: an empirical analysis in Szczecin, Poland - Sypion, Natalia; Kołodziej, Arkadiusz; Leitner, Michael; Dutkowski, Marek (Bulletin of Geography. Socio-economic Series, 2024)
The study of the fear of crime phenomenon provides a socially and politically important research question. Many studies show that gender differentiates the fear of crime, which is why we examine this phenomenon in a spatial perspective. The female versus male perspective of feelings of safety in residential areas were significantly different. The research was carried out using the CAWI technique in the city of Szczecin, in Poland (n=346). The research also examined which factors influenced the fear of crime the most: darkness, socio-economic characteristics, type of violations, number of registered crimes, or the assessment of police work. The research shows that women aged 19–25 are the group that reports the highest fear of crime. They are generally better educated, work or study, but often come from peripheral rural areas, and their current place of residence is little known. Activities aimed at building a sense of security in local communities should therefore be addressed to a wide demographic spectrum of recipients, but with emphasis on young females. A very interesting result from the research is the relationship between fear of crime and the opinion of residents about the effectiveness of police work, where the study reports that the better the assessment of police work, the lower the fear of crime.